Pengembangan Media Pembelajaran IPAS Berbantuan KineMaster Materi Siklus Air di Kelas IV Sekolah Dasar - Annisa, Arrahimmi Nur Ahadu; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research is motivated by the lack of availability of IT-based learning media that can motivate and attract students' interest in learning. This research aims to develop video media assisted by KineMaster in science learning that is valid and practical. This research is development research (R&D) with the ADDIE development model. The response questionnaire consists of a teacher response questionnaire and a student response questionnaire. The test subjects in this research were 26 students consisting of 13 men and 13 women in class IVC at SDN 23 Marapalam. The results of the video media development research obtained obtained a validity level of 87.5% for material, 81.25% for language and 88.53% for media in the valid category. The results of the response questionnaire at school show that the learning media is very practical with the results of the teacher response questionnaire obtaining a practicality percentage of 93%. Meanwhile, the results of the student response questionnaire were with a practicality percentage of 93%. Thus, it can be concluded that the science learning media assisted by KineMaster on the water cycle material in Class IV Elementary School has been declared valid and practical for use in learning.